(untitled) (Crossing the Border: International Journal of Interdisciplinary Studies, 2014)
This research explores the growth performance of three potential medicinal plants namely, Bajradanti (Potentilla flugens), Chutro (Breberisaristata), and Timur (Xanthoxylumarmatum) cultivated at nursery of Institute of Forestry with the application of tunnel, shaded and open beds treatment each with 4.0 m x 1.0 m size and constant supportive facilities of manure, irrigation and care. From the measurement of ten months growth performance, B. Aristata and X. armatum showed their better growth in open bed than shed and tunnel beds, unlike P. Flugens showed better performance in shed bed. The average growth performances per month of P. fulgens and X. armatum vary significantly with respect to applied treatments (p<0.05) but converse in the case of B. aristata when using parametric F- test based on one way analysis of variance. Determined contribution of open treatment for growth performance per month in the species indicates that natural climate is tolerable as well as favorable for thorny types of medicinal plants than that of others. DOI: http://dx.doi.org/10.3126/ctbijis.v2i1.10811 Crossing the Border: International Journal of Interdisciplinary Studies Vol.2(1) 2014: 31-40